The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.36899/japs.2021.5.0325
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Fat Sources and Energy Levels on Growth Performance, Nutrient Digestibility and Meat Quality in Broiler Chicks

Abstract: This experiment was conducted to evaluate different oil sources and energy density in broiler. Two vegetable oil sources (canola and palm oil), two animal oil sources (fish oil and refined poultry oil) and two levels of energy were: recommended energy (RE); 3000 and 3200 kcal/kg according to manual of Ross 308 and low energy (LE); 2850 and 3050 kcal/kg used in starter and finisher phases, respectively. Four hundred and sixteen (416) day-old broiler birds were distributed in eight treatments (four replicates co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 17 publications
(22 reference statements)
0
3
0
Order By: Relevance
“…Skrivan et al (2000) showed that feeding 0.5% lard oil in broilers diet had improved WG (1973 vs 1799 g) than those on 0.5% rapeseed oil. Shoaib et al (2021b) observed that poultry fat had higher digestibilities of EE (69 vs 64 and 63%) and CP (65 vs 61%) than fish and palm oil. Birds fed diet supplemented with palm oil had higher phosphorus digestibility than those fed linseed and soybean oil (Abdulla et al, 2016).…”
Section: Animal Fatsmentioning
confidence: 90%
See 2 more Smart Citations
“…Skrivan et al (2000) showed that feeding 0.5% lard oil in broilers diet had improved WG (1973 vs 1799 g) than those on 0.5% rapeseed oil. Shoaib et al (2021b) observed that poultry fat had higher digestibilities of EE (69 vs 64 and 63%) and CP (65 vs 61%) than fish and palm oil. Birds fed diet supplemented with palm oil had higher phosphorus digestibility than those fed linseed and soybean oil (Abdulla et al, 2016).…”
Section: Animal Fatsmentioning
confidence: 90%
“…A range of animal fat sources is utilised in poultry diets to fulfil the energy requirement of birds i.e., tallow, lard and poultry fat. Shoaib et al (2021b) observed that poultry fat had lower feed intake (3134 vs 3304 and 3278 g), higher weight gain (1832 vs 1789 and 1741 g) and improved FCR (1.72 vs 1.84 and 1.88) than fish and palm oil. Shahryar et al (2011) revealed that addition of canola oil and poultry fat at 3% in broilers diet had higher weight gain (PF: 2000 g, CO: 1965 g) and better FCR (PF: 1.70, CO: 1.74).…”
Section: Animal Fatsmentioning
confidence: 92%
See 1 more Smart Citation